Red seaweed extract as a phycological biostimulant enhances groundnut drought tolerance: Integrated agronomic, physiological, and UAV-based insights - Malihatun Nesa; Sudip Sen; Md. Farhadur Rahman; Md. Moshiul Islam; S. M. Rafiquzzaman; Md. Main Uddin Miah; Abdul Kaium Tuhin; Hasan Muhammad Abdullah (Journal of Applied Phycology, 2026)

State disaggregation for Non-Intrusive Load Monitoring (NILM) with calibrated bagged Seq2Point 1D convolutional neural networks - Md Mahadi Hasan Imran; Muhamad Zalani Daud; Muhammad Mukhtar Qureshi; Shahrizan Jamaludin; Atta-ur-Rahman; Md Meherullah; Abdullah Alqahtani (Energy and Buildings, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

Water footprint assessment under deficit irrigation: a comparative analysis of field data and CROPWAT model agreement in semi-arid regions - Hasan Er; Halit Tutar; Ilker Angin; Abdullah Muratoglu; Mehdi Rahimi; Muhammad Farooq (Irrigation Science, 2026)

Synergistic Sedative Activity of Indirubin on Diazepam in Thiopental Sodium-induced Sleeping Mice: A Potential GABAergic Transmission - Tamanna Khatun; Abdul Malik; Abdullah K. Alshememry; Rubel Hasan; Md.Shimul Bhuia; Raihan Chowdhury; Sabiha Fatima; Dipu Bishwas; Sonaly Akter Mukty; Ishrat Jahan Disha; Mehedi Hasan Bappi; Muhammad Torequl Islam (Molecular Neurobiology, 2025)

Antiemetic Efficacy of Nodakenin Through Muscarinic, Dopaminergic, and Serotonergic Receptor Modulation: Combined Experimental and Computational Approach - Towfiqur Rahman; Feroz Khan Nun; Tawfik Rakaiyat Ripu; Md. Sakib Al Hasan; Md. Shakil Ahmmed; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Imam Hossen Rakib; Emon Mia; Md. Shimul Bhuia; Muhammad Torequl Islam (Cell Biochemistry and Biophysics, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Exploration and evaluation of antioxidant activity in isolated phenolics from Jasminum scandens (retz) vahl - Afsin Malik; Faria Mannan Mithi; Sania Ashrafi; Muhammad Abdullah Al-Mansur; Monira Ahsan; Choudhury Mahmood Hasan; A.T.M. Zafrul Azam (Natural Product Research, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Combined effects of ternary oxides (Mg-Cu-O) and jute stick derived activated carbon for hydrogen storage in MgH2 - Mehedi Hasan; Deboshree Rani Mukta; Abdullah Mohammad Sarjish; Stefano Enzo; Muhammad Nurunnabi Siddiquee; Mohammad Mozahar Hossain; Victoria Padilla; Mohammed Jasim Uddin; Wasikur Rahman (Environmental Science and Pollution Research, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Reshaping the healthcare world by AI-integrated wearable sensors following COVID-19 - Bangul Khan; Rana Talha Khalid; Khair Ul Wara; Muhammad Hasan Masrur; Samiullah Khan; Wasim Ullah Khan; Umay Amara; Saad Abdullah (Chemical Engineering Journal, 2025)

Adenosine A2AR in viral immune evasion and therapy: unveiling new avenues for treating COVID-19 and AIDS - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Sajjad Ullah; Abualgasim Elgaili Abdalla; Muhammad Ikram Ullah; Bi Bi Zainab Mazhari; Lienda Bashier Eltayeb; Ismail Hamad; Hasan Ejaz (Molecular Biology Reports, 2024)

Evaluating climate change impacts on reef environments via multibeam echosounder and Acoustic Doppler Current profiler technology - Mohd Azhafiz Abdullah; L.F. Chuah; Razak Zakariya; Asad Syed; Rozaimi Che Hasan; Shahrul Miza Mahmud; Abdallah M. Elgorban; A. Bokhari; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman (Environmental Research, 2024)

Impact of extreme weather events on mental health in South and Southeast Asia: A two decades of systematic review of observational studies - Muhammad Mainuddin Patwary; Mondira Bardhan; Md Atiqul Haque; Syed Moniruzzaman; Johanna Gustavsson; Md Maruf Haque Khan; Jenni Koivisto; Marium Salwa; Saidur Rahman Mashreky; A.K.M. Fazlur Rahman; Anika Tasnim; Md Redwanul Islam; et al. (Environmental Research, 2024)

Effect of the number of Cyperus rotundus and medium height on the performance of batch-constructed wetland in treating aquaculture effluent - Muhammad Fauzul Imron; Wa Ode Ayu Hestianingsi; Trisnadi Widyaleksono Catur Putranto; Nita Citrasari; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Setyo Budi Kurniawan (Chemosphere, 2024)

Quantifying canopy nitrogen of Aman rice utilizing multi-temporal unmanned aerial systems - Maruf Hossain; Hasan Muhammad Abdullah; Tanvir Ahmmed; Md Giashuddin Miah; Moin Us Salam; Majharul Islam; Md Mizanur Rahman (Remote Sensing Applications: Society and Environment, 2024)

Long-term quantification of pre and post-monsoon surface water area of Bangladesh - Syed Muhimeen Ahmed; Hasan Muhammad Abdullah; Tahsin Tanha Chowdhury; Abiar Rahman; Mohammad Zahangeer Alam (Remote Sensing Applications: Society and Environment, 2023)

Antiemetic effects of sclareol, possibly through 5-HT3 and D2 receptor interaction pathways: In-vivo and in-silico studies - Mehedi Hasan Bappi; Abdullah Al Shamsh Prottay; Khattab Al-Khafaji; Md Showkoth Akbor; Muhammad Kamal Hossain; Md Shahazul Islam; Afia Ibnath Asha; Cassio Rocha Medeiros; Catarina Martins Tahim; Elaine Cristina Pereira Lucetti; Henrique Douglas Melo Coutinho; Hossam Kamli; et al. (Food and Chemical Toxicology, 2023)

Anxiolytic-like effect of succinic acid: A possible GABAergic intervention - Md. Nayem Mia; Shanita Zaman Smrity; Mehedi Hasan Bappi; Hossam Kamli; Tawhida Islam; Abdullah Al Shamsh Prottay; Md. Showkoth Akbor; Md. Abdul Latif; Shoriful Islam; Kushal Bhakta; Manik Chandra Shill; Francisco Claudeni Pereira de Sousa; et al. (Food Bioscience, 2023)

Phytochemical screening and evaluation of antioxidant, anti-inflammatory, antimicrobial, and membrane-stabilizing activities of different fractional extracts of Grewia nervosa (Lour.) Panigrahi - Mehanaz Islam; Abdullah Al Shamsh Prottay; Irin Sultana; Abdullah Al Faruq; Mehedi Hasan Bappi; Md. Showkoth Akbor; Afia Ibnath Asha; Md. Munnaf Hossen; Pedro Esau Macedo Machado; Inacio Jose Secundo Junior; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Food Bioscience, 2023)

Coagulation–flocculation of aquaculture effluent using biobased flocculant: From artificial to real wastewater optimization by response surface methodology - Setyo Budi Kurniawan; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah; Ahmad Razi Othman; Hassimi Abu Hasan (Journal of Water Process Engineering, 2023)

A changing coastal ecosystem: Cox’s Bazar in southeastern coastal region of Bangladesh - Md. Giashuddin Miah; Md. Rafiqul Islam; Joyashree Roy; Md. Mezanur Rahman; Hasan Muhammad Abdullah (Environment, Development and Sustainability, 2023)

Investigation of PT 58 and PEG-6000-based finned heat sinks for thermal management of electronics - Radhi Abdullah Lawag; Hafiz Muhammad Ali; Md Hasan Zahir; Bilal A. Qureshi (Journal of Cleaner Production, 2023)

Phytotechnology for domestic wastewater treatment: Performance of Pistia stratiotes in eradicating pollutants and future prospects - Muhammad Fauzul Imron; Abiyyu Armijn Firman Firdaus; Zhiella Octabriani Flowerainsyah; Dzikro Rosyidah; Nurina Fitriani; Setyo Budi Kurniawan; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Yudha Gusti Wibowo (Journal of Water Process Engineering, 2023)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Plant-based coagulants/flocculants: characteristics, mechanisms, and possible utilization in treating aquaculture effluent and benefiting from the recovered nutrients - Mohammad Mohammad Alnawajha; Setyo Budi Kurniawan; Muhammad Fauzul Imron; Siti Rozaimah Sheikh Abdullah; Hassimi Abu Hasan; Ahmad Razi Othman (Environmental Science and Pollution Research, 2022)

Exploring standardized precipitation evapotranspiration index for drought assessment in Bangladesh - Md Giashuddin Miah; Hasan Muhammad Abdullah; Changyoon Jeong (Environmental Monitoring and Assessment, 2017)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Monitoring the drastic growth of ship breaking yards in Sitakunda: a threat to the coastal environment of Bangladesh - Hasan Muhammad Abdullah; M. Golam Mahboob; Mehmuna R. Banu; Dursun Zafer Seker (Environmental Monitoring and Assessment, 2013)